Singapore-Malaysia Ties : What Lies Ahead in the Post-KTM Era? - Yang Razali Kassim (2018)
One of the most productive bilateral retreats between Singapore and Malaysia since the series began took place this week at the Istana in Singapore. How will the agreements be affected by the upcoming Malaysian general election?